Redefining Performance in Hybrid Public Organisations: The Case of French Prisons - Laurine Basse; Anaïs Saint Jonsson (Public Administration Quarterly, 2026)
Hybrid public organisations are characterised by the coexistence of multiple institutional logics, which are sometimes contradictory. However, there has been little theoretical work on how this hybridity shapes organisational performance. Existing performance management systems tend to fragment these logics rather than articulate them, and the mechanisms by which logics translate into performance criteria in a public hybrid are not well understood. Drawing on the institutional logics perspective and the value creation framework, this article examines French prisons as a case study of segmented hybrid organisations. Using a qualitative methodology combining 47 interviews, 47 days of non-participant observation and 50 institutional documents, we address the following questions: How does institutional hybridity translate into performance criteria, and how do current performance management mechanisms affect hybridity in turn? Our findings reveal that reconciling contradictory institutional logics constitutes a performance criterion. We further observe a differentiated distribution of institutional logics across performance dimensions, with internal dimensions mobilising a broader plurality of logics than external ones.